Evaluation of Modern Sedimentation Processes in a Proglacial Lake: Linnévatnet, Spitsbergen, Svalbard, 2008 - Patrice F. Cobin (Arctic Data Center, 2013)
Cores from proglacial lake, Lake Linné, on Svalbard contain varves that hold important information about past climate change. By establishing a relationship between modern sedimentation and measured environmental conditions, we hope to calibrate the late Holocene sediment record found in Lake Linné. Since 2003 sediment trap moorings at five locations in the lake have provided proximal to distal records of overall lake sedimentation. Each mooring also had multiple traps positioned at various water depths, providing insights into the sediment distribution processes in the basin. Trap data show a clear proximal to distal decrease in sediment accumulation and grain size. The data also show an increase in sediment accumulation and grain size as water depth increases. In the most proximal traps, the finest sediment is found at the traps bottom in a very thin layer. It is followed by an abrupt increase in particle size, which grades to the coarsest sediment found in each trap. During May of 2007, prior to the spring melt, sediment traps were deployed, and an automated camera was set-up to take pictures of the inflow into the lake. The spring traps do not record any of the fine sediment found in the bottom of the yearly traps, suggesting that the majority of sediment in the yearlong traps was deposited during/after the spring melt. In addition to the spring traps and camera, snow sensors and meteorological data associate the abrupt increase in particle size with the loss of the snow pack during the spring melt. After the loss of the snowpack, other pulses of coarse sediment are linked to rainfall events in the valley. In contrast, the sediment collected at the top of the traps in July and August, the height of the ablation season, has a finer texture (fine silt and clay). These findings are consistent with data from previous years, suggesting that for systems like Lake Linné, silt laminations are related to high stream discharge events, resulting from the loss of snow pack and large rain events. The annual clay layer thickness is related to the amount of annual glacier ablation, indicating that the thickness of the clay laminations in the lake cores may be the best proxy for reconstructing late Holocene glacier mass balance. The thickness and the texture of the corresponding silt laminations are related to the environmental conditions, sediment that is remobilized in the fluvial system during high discharge events.